Criminal responsibility of the real estate portfolios in the scope of real estate books - Bellarou, Kamel (Journal of Human Sciences, 2021)
Through this study, we dealt with the penal responsibility of the conservator of mortgages within the scope of the land registry as the only basis for proving the land ownership in the light of the Algerian legislator that embrace the  real land publicity system. Our aim from this study is at first to show the concept of the land registry, its nature and the extent of its authentic confirmation as a principle of the real land publicity system. Then we aim to highlighting the penal responsibility of the conservator mortgages as a public employee granted extensive powers by the algerian legislator, through which he supervises the real estate governorate that works to prepare and deliver the state regestry. The fact that the Algerian legislator has not limited and precisely defined the legal texts that clarify the responsibility of the  estate conservator of mortgages and indicate the penalties that must be applied to every breach or bypass issued by him.